Energy Provision, Tissue Utilization, and Weight Loss in Prolonged Starvation - Runcie, J. (1974)
Daily weight loss measurements in 76 fasting, obese patients (58 females, 18 males) have shown a characteristic pattern of rapid loss initially (up to day 14) followed by a slower but uniform reduction in weight. There were significant sex differences. Measurements of tissue breakdown showed that the initial rapid weight loss was due to the continuing utilization by the nervous system of glucose derived from lean tissue. This requirement fell noticeably from the second week of starvation. Irreversible fluid elimination also contributed to the initial phase of rapid weight loss. Fat remained the primary source of energy throughout starvation and in established fasting (more than 14 days) contributed 96% of that requirement.